Persepsi Tenaga Kesehatan Terhadap Pentingnya Keberadaan Hospice Care Untuk Pasien Kanker Stadium Terminal di RSUP Fatmawati Jakarta. - Ngakili, Okky Rachmad; Mulyanto, Moch. Prasetyo (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2017)
Hospice care is an integrated service that focused in giving full support to the patients for having enjoyable life and peaceful end of life. The research aimed to find medical professional’s perception on the meaning, benefit and challenge on hospice care as well as multidisciplinary team roles in hospice care service for terminal illness patient in Fatmawati Central General Hospital, Jakarta. This Research utilized qualitative methodology with hermeneutic phenomenology approach. The participants were recruited through purposive sampling according to the inclusive criteria. A total number of 15 main participants consisted of 3 persons in each proffesion namely doctor, nurse, nutriciant, physiotherapist and pharmacist. A focus group discussion in the research and education room. The analyzed through N VIVO 11 program, interpreted within thematic and sub-theme analysis. The result showed that hospice care was very important. The health professionals stated that multidisciplinary team’s roles in Hospice care acted as educator, consellor and care giver to respond to patients needs. It was concluded then that hospice care is important to improve patients quality of life in many aspects. The research recommended the hospice care to be implemented and supported by health care team and management of Fatmawati Central General Hospital Jakarta.Keyword: Perception, Medical Proffesional, Hospice Care.